EdTech for Ugandan girls: Affordances of different technologies for girls' secondary education during the Covid-19 pandemic - Damani, Kalifa; Daltry, Rebecca; Jordan, Katy; Hills, Libby; Evans, Laura (Development Policy Review, 2022)
Motivation This article discusses the use of educational technology (EdTech) in girls' education at PEAS (Promoting Education in African Schools) schools in rural Uganda during the Covid-19-related school closures. Purpose This article addresses a research gap surrounding the potential use of EdTech to support girls' education, focusing on the barriers to girls' EdTech use and how technology might be used to enhance girls' education in disadvantaged rural areas—specifically their academic learning and their social and emotional learning. Methods and approach A sequential, explanatory mixed-methods case-study approach was used. Quantitative exploration of a dataset of 483 Ugandan students, from 28 PEAS schools, was first conducted, followed by interviews with PEAS staff to elucidate the reasons and context behind the findings. Findings Findings show that female students are less likely than male students to have access to their caregivers' phones for learning. The form of EdTech that appeared to be most beneficial for girls' academic learning was radio; girls also had significantly more interest in tuning into radio broadcasts than boys did. Also, poorer boys were more likely to be influenced by SMS messages than wealthier boys. Apart from gender-based differences, students with more highly educated parents found SMS messages more helpful, and phone calls from teachers appeared to help boost younger students' self-confidence. Policy implications The findings suggest that policy-makers need to: carefully consider provision of education through multiple modes of EdTech in order to ensure that it reaches all students; ensure that caregivers are involved in the strategies developed for girls' education; make EdTech interventions interactive; and consider language in EdTech interventions. Given the gender differences which emerged, the findings are of relevance both to supporting the continuation of educational provision during periods of school closure, and also in terms of finding additional ways to support girls' education alongside formal schooling.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12619 KerkoCite.ItemAlsoKnownAs: 2339240:XVDEX345 2405685:AV99SN2V 2405685:RQ6VBJVK 2405685:S7XK6HFJ
Keywords: Covid-19; EdTech; education; gender; rural Uganda

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech and girls education in low- and middle-income countries: which intervention types have the greatest impact on learning outcomes for girls? - Jordan, Katy; Myers, Christina (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5874080 2405685:9RGDIIHD
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Publisher: Net Journals ERIC Number: EJ1373064 KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.104.22.048 10.5281/zenodo.5863400 10.53832/edtechhub.0097 2339240:6EFQH53V 2339240:7QAZINAG 2405685:49EBMKRI 2405685:GXZHRRYW 2405685:YXFLNITE
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M7XYZTWF 2405685:C7C3BM9Z

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen